2001
DOI: 10.1039/b007839p
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental parameters on the accuracy of nitrogen dioxide passive diffusion tubes for ambient measurement

Abstract: Two studies at three sites in the UK provided confirmation that systematic positive bias in NO2 diffusion tube measurement occurred because of changes to "within-tube" chemistry, rather than eddy diffusion at the mouth of the tube. In the first study in Cambridge, UK, sampler overestimation for 1 and 2 week exposures was compared to corresponding time-averaged monitor measurements (NO-NO2-NOx, O3) and weather variables. Noninearity between sampler and monitor NO2 measurements was interpreted in terms of spatia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
15
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 11 publications
6
15
0
Order By: Relevance
“…Atkins et al (17) saw no effect of wind speed in the range 1.0 to 4.5 m/s for 1 week exposure of Palmes tubes. A similar lack of correlation with wind speed has been reported by other authors for outdoor samplers (21,30), although unsheltered diffusion tubes have shown larger (up to 18%) apparent sampling rates than adjacent sheltered tubes (32,33), which may be an effect of wind speed or turbulence. Similar lower sampling rates in sheltered tubes compared with adjacent unsheltered tubes have been noted in other studies (27).…”
Section: The Role Of Meteorological Conditions During Sampling Windspeedsupporting
confidence: 61%
See 1 more Smart Citation
“…Atkins et al (17) saw no effect of wind speed in the range 1.0 to 4.5 m/s for 1 week exposure of Palmes tubes. A similar lack of correlation with wind speed has been reported by other authors for outdoor samplers (21,30), although unsheltered diffusion tubes have shown larger (up to 18%) apparent sampling rates than adjacent sheltered tubes (32,33), which may be an effect of wind speed or turbulence. Similar lower sampling rates in sheltered tubes compared with adjacent unsheltered tubes have been noted in other studies (27).…”
Section: The Role Of Meteorological Conditions During Sampling Windspeedsupporting
confidence: 61%
“…In their modelling of the situation, the authors took no account of chemical reactions inside the tube during sampling, which may have affected the apparent sampling rates outdoors. More recent experiments outdoors with tubes of different lengths and of different materials (acrylic vs. quartz) (21) showed no effect of diffusion length for quartz samplers at 120 or 71 mm, implying no effect of wind shortening, although enhanced sampling attributed to wind shortening was observed for the shortest diffusion length (40 mm). The difference between the different tube materials was dependent on tube length.…”
Section: The Role Of Meteorological Conditions During Sampling Windspeedmentioning
confidence: 88%
“…Pollutant uptake by passive samplers can be affected by meteorological conditions, such as temperature, relative humidity, and air movement at the surface (Tang et al, 1997(Tang et al, , 1999Tang and Lau, 2000;Krupa and Legge, 2000;Tang, 2001;Kirby et al, 2001;Partyka et al, 2007;Fraczek et al, 2009;Salem et al, 2009;Zabiegala et al, 2010), as well as radiation (Krupa and Legge, 2000). Seasonality can also influence the performance of passive samplers (Logan, 1985;Legge and Krupa, 1990;Tang et al, 1997;Krupa and Legge, 2000).…”
Section: Introductionmentioning
confidence: 96%
“…The passive diffusion tube has been used for many years to measure outdoor concentrations of NO 2 across rural (Atkins and Lee, 1995) and urban (Campbell et al, 1994) national networks, and for more local scale concentration variations (Reeuwijk et al, 1998;Kirby et al, 2001). The increased emphasis on NO 2 as an air pollutant is partly a result of the fact that concentrations of NO 2 in urban areas have not declined in recent years, and the current requirement for some local authorities to review air quality in their areas makes it likely that the use of passive samplers will increase for compliance with wide-area assessment of NO 2 .…”
Section: Introductionmentioning
confidence: 99%